-4,-4 - 9,-1 is the answer, i think
Answer:
B
Step-by-step explanation:
The inverse of function f(x) = 9x+7 is f-1(x) = x/9 - 7/9
<h3>How to determine the inverse of the function?</h3>
The function is given as:
f(x) = 9x + 7
Express f(x) as y
y = 9x + 7
Swap the positions of x and y in the above equation
x = 9y + 7
Subtract 7 from both sides
9y = x - 7
Divide through by 9
y = x/9 - 7/9
Express as an inverse function
f-1(x) = x/9 - 7/9
Hence, the inverse of function f(x) = 9x+7 is f-1(x) = x/9 - 7/9
Read more about inverse functions at:
brainly.com/question/14391067
#SPJ1
199.
the z score for the 90th percentile is 1.28, so you can solve the equation
which gets you the 199